The Theory of Optimal Taxation: What is the Policy Relevance? - Peter Birch Sørensen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2006)
The paper discusses the implications of optimal tax theory for the debates on uniform commodity taxation and neutral capital income taxation. While strong administrative and political economy arguments in favor of uniform and neutral taxation remain, recent advances in optimal tax theory suggest that the information needed to implement the differentiated taxation prescribed by optimal tax theory may be easier to obtain than previously believed. The paper also points to the strong similarity between optimal commodity tax rules and the rules for optimal source-based capital income taxation.
Keywords: H21; H25; 330; optimal taxation; uniform taxation; tax neutrality